Element of students’ creative thinking skills: A critical evaluation of senior high school Indonesian textbooks - Huda, Miftakhul; Sulisyono, Yunus; Aswadi , Aswadi; Soleh , Anjas Rusdiyanto; Retikae, Nadhiya Dwiksan (Universitas Ahmad Dahlan, 2025)
This research aims to critically evaluate high school Indonesian language textbooks from the perspective of developing students' creative thinking. The type of research in this study is qualitative. The research design used is a case study. Primary data was obtained directly from Indonesian language textbooks used in high school. Secondary data includes related documents, such as curriculum, textbook development guidelines, and relevant academic literature. The data collection technique is an intensive reading technique. The data analysis technique in this research involves several stages. The first stage is transcription and organizing data. The second stage is thematic analysis. The third stage is data triangulation. The fourth stage is interpretation and preparation of the report. The research results show that this book has been prepared in accordance with national curriculum standards and covers various basic competencies. Several aspects still need to be improved to better support the development of students' creative thinking. The tasks are dominated by mechanical activities, so they do not fully support the development of critical and creative thinking. Apart from that, the relevance of the material to actual issues and students' real lives is still lacking.